2020
DOI: 10.1161/jaha.119.015261
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Role of Receptor for Advanced Glycation End Products in Calcified Aortic Valve Stenosis

Abstract: Background Aortic stenosis ( AS ) is highly prevalent in patients with atherosclerotic cardiovascular disease. Advanced glycation end products ( AGE s) and the receptor for AGE s ( RAGE ) play a pivotal role for vascular calcification in atherosclerosis. We hypothesize that the AGEs– RAGE axis could also be involved in the pathophysiological mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Baseline characteristics of participants with AS, with and without type 2 diabetes, are shown in Table 1. The median duration of diabetes was 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years and 36 (72%) individuals had HbA 1c ≥48 mmol/mol (≥6.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline characteristics of participants with AS, with and without type 2 diabetes, are shown in Table 1. The median duration of diabetes was 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years and 36 (72%) individuals had HbA 1c ≥48 mmol/mol (≥6.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Hyperglycaemia has been proposed as one of the metabolic states enhancing aortic valve fibrosis and calcification [12][13][14] through a complex mechanism involving increased valvular protein glycation, of reactive oxygen species (ROS) generation, inflammation and coagulation activation [15,16]. Although the pivotal mechanism leading to such dysregulation is not fully understood, formation of AGEs has been suggested as a factor initiating and/or escalating valvular calcification [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry analysis of AS valves revealed that concomitant DM was associated with an increased percentage of C-reactive protein-positive areas and correlated with the percentage of TF-positive areas [7]. Moreover, increased valvular protein glycation due to an accumulation of advanced glycoxidation end products (AGEs) has been suggested as a contributor to faster AS progression [54][55][56][57]. AGEs are a heterogonous group of proteins or lipids irreversibly glycated by the attachment of reducing sugars onto the free amino groups.…”
Section: Molecular Links Between As and Dmmentioning
confidence: 99%
“…4,5 Studies have also suggested that the receptor of CML may play a role in the pathogenesis of calcified aortic stenosis. 6 This evidence suggests that CML plays an important role in the occurrence and development of diabetic AC.…”
Section: Introductionmentioning
confidence: 96%